Stem Cells: Innovations, Applications, and Future Directions - Tejaspreet Kaur; Nazia Khan; Zameer Pasha; Ramdas Bhat; Deepti Virupakshappa; Rajashekhara Bharisharanesha; Ritik Kashwani (Journal of Pharmacy and Bioallied Sciences)
Stem cells offer great promise in dentistry by regenerating critical oral tissues. Derived from sources such as dental pulp, periodontal ligament, and dental follicle, these cells can be pluripotent or multipotent and are capable of differentiating into various cell types, including odontoblasts and osteoblasts. This regenerative potential could transform treatments for dental conditions like periodontal disease and pulpitis. Advancing this field requires understanding stem cell differentiation and exploring tissue engineering and biomaterial scaffolds. Despite the potential, evolving legal and ethical issues shape the integration of these innovations. Research in dental stem cells represents a significant advance in regenerative medicine, promising to enhance dental treatments and patient care.